2003
DOI: 10.1002/ijc.11563
|View full text |Cite
|
Sign up to set email alerts
|

Retargeting of adenoviral infection to melanoma: Combining genetic ablation of native tropism with a recombinant bispecific single‐chain diabody (scDb) adapter that binds to fiber knob and HMWMAA

Abstract: Gene therapy is an emerging and promising modality for the treatment of malignant melanoma and other neoplasms for which conventional therapies are inadequate. Various therapeutic genes have shown promise for tumor cell killing. However, successful gene therapy depends on the development of efficient and targeted gene transfer vectors. Here we describe a novel strategy for targeting of adenovirus-mediated gene transfer to melanoma cells. This strategy combines genetic ablation of native adenoviral tropism with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 46 publications
0
56
0
Order By: Relevance
“…Primary melanoma cells were obtained from surgically removed skin metastasis as described previously. 8 Cells were grown at 37°C in a humidified atmosphere of 5% CO 2 . Monocyte-derived dendritic cells (moDC) were generated from leukapheresis products of healthy donors in a standardized procedure as described previously.…”
Section: Cell Culture and Generation Of Dcs And T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary melanoma cells were obtained from surgically removed skin metastasis as described previously. 8 Cells were grown at 37°C in a humidified atmosphere of 5% CO 2 . Monocyte-derived dendritic cells (moDC) were generated from leukapheresis products of healthy donors in a standardized procedure as described previously.…”
Section: Cell Culture and Generation Of Dcs And T Cellsmentioning
confidence: 99%
“…First, previous studies have revealed a paucity of expression of the adenovirus serotype 5 (Ad5) receptor CAR (coxsackievirus and adenovirus receptor) on cancer cells, which were freshly purified from tumor specimen of different tumor types. 7,8 These cells are therefore poorly infected and lysed by oncolytic adenoviruses derived from Ad5. 9,10 Secondly, animal experiments have shown that adenovirus lateralization is limited by anatomical barriers such as connective tissue, 11 which can constitute large fractions of human tumors.…”
mentioning
confidence: 99%
“…Finally, the effective transcriptional regulation afforded by PFLPS could be combined with current methods of transductional regulation including manipulation of Ad fiber knob [41][42][43][44][45][46][47] and use of bi-specific antibodies 38,[48][49][50][51] to further improve the targeting of gene therapy vectors to specific cell types and therefore increase the specificity and the safety of the vectors.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] Bridging, bispecific targeting molecules comprising either an anti-adenovirus scFv or the Coxsackievirus-adenovirus receptor linked to a targeting scFv, have been used for targeting oncolytic adenoviruses. [23][24][25][26][27][28][29] Results from a number of studies with HSV-1 have shown that it is possible to alter the tropism by incorporating ligands such as erythropoietin, interleukin (IL) 13, human hepatitis B virus preS1 peptide, the N-terminal fragment of urokinase-type plasminogen activator or 6-His into the viral envelope as glycoprotein fusion proteins. [30][31][32][33][34][35] Targeting has also been achieved using a soluble adapter molecule comprising an antiepidermal growth factor receptor (EGFR) scFv linked to the HSV-1 gD-binding domain of nectin-1 and more recently, a scFv against HER2/neu incorporated into the N terminus of gD has been shown to redirect the tropism of HSV-1 to this mammary tumour receptor.…”
Section: Introductionmentioning
confidence: 99%